2019 novel‐coronavirus: Cardiovascular insights about risk factors, myocardial injury, therapy and clinical implications. Issue 4 (1st December 2020) - Cappannoli, Luigi; Scacciavillani, Roberto; Iannaccone, Giulia; Anastasia, Gianluca; Di Giusto, Federico; Loria, Valentina; Aspromonte, Nadia
Abstract: From December 31st, 2019, a novel highly pathogenic coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), has spread worldwide, reaching at present the dimension of a pandemic. In addition to damaging the lungs, SARS‐CoV‐2 may also damage the heart and this is corroborated by the evidence that cardiovascular comorbidities are associated with a higher mortality and poor clinical outcomes in patient infected by the virus. During the infection myocardial injury, myocarditis and arrhythmias have also been reported, but the pathophysiological mechanisms of these complications are yet to be understood. Great attention is also being posed on the potential beneficial/harmful role of angiotensin converting enzyme (ACE) inhibitors, as far as the virus binds to ACE2 to infect cells, but evidences lack. Furthermore, SARS‐CoV‐2 can also affect the aspect of acute coronary syndromes, not only because these two distinct pathological entities share pathogenic aspects (such as the systemic inflammatory state and cytokine release), but also and above all for the consequences that the need to contain the infection has on the management of cardiological urgencies. The aim of this review was therefore to summarize the relationship between the virus and the cardiovascular system.